1989
DOI: 10.1128/iai.57.5.1457-1464.1989
|View full text |Cite
|
Sign up to set email alerts
|

Antipneumococcal effects of C-reactive protein and monoclonal antibodies to pneumococcal cell wall and capsular antigens

Abstract: Antibodies to pneumococcal capsular polysaccharides are well known for their ability to protect against pneumococcal infection. Recent studies indicate that antibodies to cell wall antigens, including pneumococcal surface protein A and the phosphocholine (PC) determinant of teichoic acids as well as human C-reactive protein (which also binds to PC), can protect mice against pneumococcal infection. In the present study we compared the protective effects of these agents as measured by mouse protection, the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…However, a large increase in IgG3 antibody was not observed in previous studies. IgG3 is normally present only in very low concentrations and tends to be produced following immunization with polysaccharides, which are thymus-independent antigens (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a large increase in IgG3 antibody was not observed in previous studies. IgG3 is normally present only in very low concentrations and tends to be produced following immunization with polysaccharides, which are thymus-independent antigens (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Briles et al showed that IgG3 antibody is especially protective against pneumococcal infections in mice (7). In later studies, however, they showed that the other IgG isotypes can also be protective (8,9). Studies on the role of various isotypes of antibody in protection have been hampered by the paucity of experimental models.…”
Section: Imentioning
confidence: 99%
See 1 more Smart Citation
“…Pn also elicits antibody specific for various structures on the bacterial surface, which includes the pneumococcal capsular polysaccharide (PPS) 7, the cell wall C‐polysaccharide (teichoic acid), including its phosphorylcholine (PC) moieties 8 and various pneumococcal proteins including pneumococcal surface protein (PspA) 9. Adaptive immunity to pneumococcus is largely conferred by these antibodies, which synergize with the innate immune system to confer markedly enhanced host protection 10.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of CRP, complement-dependent opsonization of S. pneumoniae type 27 and pneumococcal polysaccharide-coated erythrocytes has been reported [8,9]. However, enhanced phagocytosis was only found for live S. pneumoniae type 27 with capsular bound CRP and C3 [10] and not for live S. pneumoniae type 4 which binds C3 in the cell wall in the presence of CRP [11].…”
Section: Introductionmentioning
confidence: 99%